“You Never Get a Second Chance”: First Impressions of Physicians Depend on Their Body Posture and Gender - Grün, Felix C.; Heibges, Maren; Westfal, Viola; Feufel, Markus A. (Frontiers in Psychology, 2022)
A first impression matters, in particular when encounters are brief as in most doctor-patient interactions. In this study, we investigate how physicians‘ body postures impact patients’ first impressions of them and extend previous research by exploring posture effects on the perception of all roles of a physician––not just single aspects such as scholarly expertise or empathy. In an online survey, 167 participants ranked photographs of 4 physicians (2 female, 2 male) in 4 postures (2 open, 2 closed). The results show that male physicians were rated more positively when assuming open rather than closed postures with respect to all professional physician roles. Female physicians in open postures were rated similarly positive for items related to medical competence, but they tended to be rated less favorably with respect to social skills (such as the ability to communicate with and relate to the patient). These findings extend what is known about the effects of physicians’ body postures on the first impressions patients form to judge physicians’ medical versus social competencies. We discuss practical implications and the need for more research on interaction effects of body postures and physician gender on first impressions.